Gingerbread - Oyeyemi, Helen (New York : Riverhead Books, 2019)
"The prize-winning, bestselling author of Boy, Snow, Bird and What Is Not Yours Is Not Yours returns with a bewitching and inventive novel."--
Keywords: Gingerbread. -- Fiction; Inheritance and succession -- Fiction; Formulas, recipes, etc -- Fiction; Mothers and daughters -- Fiction; Friendship in children -- Fiction; Family secrets -- Fiction; Family-owned business enterprises -- Fiction; Fairy tales -- Adaptations; London (England) -- Fiction; Magic realist fiction; Fantasy fiction